2007
DOI: 10.1303/aez.2007.97
|View full text |Cite
|
Sign up to set email alerts
|

Artificial selection of biotypes of green rice leafhopper, Nephotettix cincticeps Uhler (Homoptera: Cidadellidae), and virulence to resistant rice varieties

Abstract: A population of green rice leafhopper, Nephotettix cincticeps Uhler (GRH), was artificially selected on 5 resistant rice varieties in the laboratory. The GRH lines selected on Saikai 164, Saikai 182, and Kanto-PL 6 were able to survive and reproduce on their respective varieties. In these lines, the developmental period of nymphs was shortened by continuous selection, although in the first generation it was longer than that of the line reared on Nipponbare carrying no resistance gene. We could not establish GR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…The GRH resistance of rice plants carrying GRH2 is broken down by virulent biotypes under experimental conditions in the laboratory. In contrast, a virulent biotype that is effective against rice plants that carry GRH2 and GRH4 from Lepe dumai and C203-1 could not be identified by continuously rearing the GRH insects on the resistant rice lines (Hirae et al 2007). Due to the presence of both GRH2 and GRH4, TGRH29 plants rapidly recognize GRH invasion and subsequently activate various defense-related genes; eventually, these plants not only show strong GRH resistance but also prevent the appearance of a virulent biotype.…”
Section: Discussionmentioning
confidence: 99%
“…The GRH resistance of rice plants carrying GRH2 is broken down by virulent biotypes under experimental conditions in the laboratory. In contrast, a virulent biotype that is effective against rice plants that carry GRH2 and GRH4 from Lepe dumai and C203-1 could not be identified by continuously rearing the GRH insects on the resistant rice lines (Hirae et al 2007). Due to the presence of both GRH2 and GRH4, TGRH29 plants rapidly recognize GRH invasion and subsequently activate various defense-related genes; eventually, these plants not only show strong GRH resistance but also prevent the appearance of a virulent biotype.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, elite varieties that carry other BPH resistance gene (Bph3 or bph4) that have been widely cultivated in southeastern Asia (Khush 1989) have recently become susceptible. Virulent biotypes of the planthoppers and of leafhoppers have been experimentally identified by continuously rearing of the insects on resistant lines of rice, each of which carried a single major resistance gene (Ketipearachchi et al 1998, Hirae et al 2007). This suggests that natural strains of the insects are also likely to feed on rice plants that possess a single major gene for resistance.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that natural strains of the insects are also likely to feed on rice plants that possess a single major gene for resistance. The development of pyramided lines (PYLs) that carry multiple genes for resistance would be an effective way to delay the breakdown of GRH resistance (Hirae et al 2007) and BPH resistance (Myint et al 2009a). Deployment of PYLs can therefore be a useful tool because it can increase the durability of resistance against virulent biotypes and may even suppress the occurrence of virulent biotypes.…”
Section: Introductionmentioning
confidence: 99%
“…These genes continue to form a basis for rice resistance breeding programs in Asia; however, they are subject to planthopper and leafhopper adaptation. In recent years, virulent planthopper and leafhopper populations have been noted throughout Asia and these have rendered many major resistance genes ineffective [11,17,35,36]. For example, Horgan et al [11] indicated that the Bph1, bph2, bph5, bph7, bph8, Bph9, Bph10 and Bph18 genes are currently ineffective against planthopper populations in many parts of Asia.…”
Section: Aspects Of Virulence Adaptation In Nilaparvata Lugensmentioning
confidence: 99%